Wound healing angiogenesis: A perspective of nurse - Alia Andriany; Takdir Tahir; Elly Lilianty Sjattar; Julianus Ake; Hasanuddin Nuru (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
- Abstract is not required -